T cell epitope identification for bovine vaccines: An epitope mapping method for BoLA A-11 - Groot, A.S.; Nene, Vishvanath M.; Hegde, N.R.; Srikumaran, S.; Rayner , J.; Martin, W. (Elsevier, 2003)
T cell responses play an important role in immunity to parasites and other microbial agents of infectious diseases, therefore a number of T cell-directed vaccines are in development. Computer-driven algorithms that facilitate the discovery of T cell epitopes from protein and genome sequences are now being used to accelerate preclinical studies of human vaccines. Similar tools are not yet available for predicting T cell epitopes for animal vaccines, but there may be sufficient data available to begin the process of compiling the algorithms. We describe the construction of a novel mathematical `matrix' that describes the properties of bovine major histocompatibility complex (BoLA) system antigen (BoLA) A-11 peptide ligands, developed for use with EpiMatrix, an existing T cell epitope-mapping algorithm. An alternative means of developing BoLA matrices, using the pocket profile method, is also discussed. Matrices such as the one described here may be used to develop T cell epitope-mapping tools for cattle and other ruminants. Epitope-mapping algorithms offer a significant advantage over other methods of epitope selection, such as the screening of synthetic overlapping peptides, because high throughput screening can be performed in silico, followed by ex vivo confirmatory studies. Furthermore, using epitope-mapping algorithms, putative T cell epitopes can be derived directly from genomic sequences, allowing researchers to circumvent labor-intensive cloning steps in the genome-to-vaccine discovery pathway.